2019
DOI: 10.1021/acs.iecr.9b02847
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube/Chitosan-Based Elastic Carbon Aerogel for Pressure Sensing

Abstract: Elastic carbon materials with high compressibility are ideal candidates for flexible piezoresistive sensors. Carbon nanotubes (CNTs) are promising nanoblocks for fabricating compressible and elastic carbon aerogels because of their excellent conductivity and mechanical strength. However, insufficient interaction among CNTs makes them difficult to assemble in an elastic macrostructure. Herein, a facile yet effective method was proposed to fabricate a compressible and elastic carbon aerogel from multiwalled carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 39 publications
0
22
0
2
Order By: Relevance
“…Table S5 summarizes the literature on carbon aerogels derived from chitosan. These materials generally have microporous structures with high specific surface areas up to % 2500 m 2 g À1 , [233,234] depending on the gel preparation conditions,c alcination temperature,a nd KOHa nd/or K 2 CO 3 activation procedure.S ome applications of carbon aerogels have been proposed taking advantage of their high surface area, Nc ontent, and electrical conductivity as adsorbents (Section 5.5.1), [233][234][235] sensors, [236] and supercapacitors, [237,238] sometimes in combination with electrically conductive carbon nanotubes. [236]…”
Section: From Chitosan To Carbon Aerogelsmentioning
confidence: 99%
“…Table S5 summarizes the literature on carbon aerogels derived from chitosan. These materials generally have microporous structures with high specific surface areas up to % 2500 m 2 g À1 , [233,234] depending on the gel preparation conditions,c alcination temperature,a nd KOHa nd/or K 2 CO 3 activation procedure.S ome applications of carbon aerogels have been proposed taking advantage of their high surface area, Nc ontent, and electrical conductivity as adsorbents (Section 5.5.1), [233][234][235] sensors, [236] and supercapacitors, [237,238] sometimes in combination with electrically conductive carbon nanotubes. [236]…”
Section: From Chitosan To Carbon Aerogelsmentioning
confidence: 99%
“…These results showed that the fabrication of “green” sensor reduced the energy consumption for wearable monitoring. Except as mentioned above, other materials such as CNTs, carbon black (CB), conductive polymers, and graphene are used in combined with chitosan to fabricate the flexible strain sensors [ 88 , 89 , 90 , 91 , 92 ]. For examples, CS/CB nanocomposite sponges were fabricated via combining solution-mixing and freeze-drying methods, which presented sensitive strain sensing performance [ 88 ].…”
Section: Applications Of Biopolymers-based E-skins and Flexible Stmentioning
confidence: 99%
“…Carbon materials with good conductivity, high elasticity and extensibility are suitable candidates for flexible sensors. Luo et al have proposed a simple and effective method to build a compressible carbon aerogel from multiwalled CNTs by employing CB as a binder [ 89 ]. CB can link multiwalled CNTs into continuous lamellas and result in stable 3D structures.…”
Section: Applications Of Biopolymers-based E-skins and Flexible Stmentioning
confidence: 99%
“…Die Materialien haben im Allgemeinen mikroporçse Strukturen mit großen spezifischen Oberflächen von bis zu 2500 m 2 g À1 , [233,234] abhängig von den Herstellungsbedingungen des Gels,d en Kalzinierungstemperaturen sowie KOH-und/oder K 2 CO 3 -Aktivierungsverfahren. Einige Anwendungen wurden vorgeschlagen, welche die große Oberfläche,d en N-Gehalt und die elektrische Leitfähigkeit nutzen:A dsorptionsmittel (Abschnitt 5.5.1), [233][234][235] Sensoren [236] und Superkondensatoren, [237,238] manchmal kombiniert mit elektrisch leitfähigen Kohlenstoffnanorçhren. [236]…”
Section: Vonc Hitosan Zum Kohlenstoff-aerogelunclassified
“…Einige Anwendungen wurden vorgeschlagen, welche die große Oberfläche,d en N-Gehalt und die elektrische Leitfähigkeit nutzen:A dsorptionsmittel (Abschnitt 5.5.1), [233][234][235] Sensoren [236] und Superkondensatoren, [237,238] manchmal kombiniert mit elektrisch leitfähigen Kohlenstoffnanorçhren. [236]…”
Section: Vonc Hitosan Zum Kohlenstoff-aerogelunclassified